The Impact of ERP Systems on Financial Reporting Quality: A Systematic Literature Review - Dewi Serewaty Silalahi; Sambas Ade Kusuma; Keulana Erwin; Fahmi Natigor Nasution (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
In the era of digital transformation, Enterprise Resource Planning (ERP) systems are standard for integrated organizations, yet their impact on financial reporting quality remains debated. This study employs a Systematic Literature Review (SLR) to analyze the relationship between ERP systems and reporting quality, screening papers from 2015 to 2025 via Scopus and Google Scholar. Addressing two research questions, the study identified 68 initial records, narrowed to 10 high-quality empirical studies. Results show a publication surge in 2017 followed by fluctuating trends until 2025, primarily within the Business, Management, and Accounting sectors (37%). Qualitative synthesis reveals that ERP significantly improves timeliness and accuracy by providing a "single source of truth" and reducing manual errors. Furthermore, digital audit trails enhance faithful representation and verifiability. However, system complexity may hinder understandability without adequate staff training. Ultimately, ERP improves accounting outcomes by integrating technology with workforce skills, though success depends on organizational readiness.